2020
DOI: 10.1371/journal.pone.0240350
|View full text |Cite
|
Sign up to set email alerts
|

Using Optical Quality Analysis System for predicting surgical parameters in age-related cataract patients

Abstract: The Optical Quality Analysis System (OQAS, Visiometrics) provides objective measurements of image formed onto retina, by combining quantification of ocular media transparency and of optical aberrations. In order to evaluate its contribution in the assessment of age-related cataract, we conducted a monocentric clinical study to determine the relationships between clinical grading of lens opacity, OQAS parameters, and parameters required for cataract surgery by phacoemulsification with ultrasound (called "phacod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Optical quality was evaluated using the Optical Quality Analysis System (OQAS), which analyzes visual quality based on aberration, scatter, and diffraction 14 and uses a double-pass technique to objectively measure the image formed on the retina by merging the quantification of optical aberrations and light scattering back and forth caused by the loss of eye transparency. 15 The instrument uses a 4.0 mm pupil to measure 3 values on the OQAS, namely, the objective scatter index (OSI), modulation transfer function (MTF) cutoff, and the point spread function (PSF) expressed as the Strehl ratio. OSI, which reveals the intraocular light scatter, is calculated by sizing the sum of light on the periphery of the double-pass image based on the quantity of light on the center.…”
Section: Methodsmentioning
confidence: 99%
“…Optical quality was evaluated using the Optical Quality Analysis System (OQAS), which analyzes visual quality based on aberration, scatter, and diffraction 14 and uses a double-pass technique to objectively measure the image formed on the retina by merging the quantification of optical aberrations and light scattering back and forth caused by the loss of eye transparency. 15 The instrument uses a 4.0 mm pupil to measure 3 values on the OQAS, namely, the objective scatter index (OSI), modulation transfer function (MTF) cutoff, and the point spread function (PSF) expressed as the Strehl ratio. OSI, which reveals the intraocular light scatter, is calculated by sizing the sum of light on the periphery of the double-pass image based on the quantity of light on the center.…”
Section: Methodsmentioning
confidence: 99%
“…Different scholars have different views about the extent to which residual spherical aberration can affect postoperative visual satisfaction. Garcin et al ( 32 ) used the optical quality analysis system (OQAS) visual quality assessment system to study the postoperative visual quality with zero spherical aberration IOL. The authors reported that the best corrected visual acuity and contrast sensitivity were significantly improved after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It showed a correlation between intra-operative phacodynamics and cataract level grading. Garcin et al recently published their correlation of Optical Quality Analysis system (OQAS Visiometrics) parameters with surgical parameters for age-related cataracts [16]. The OQAS provides objective measurements of the image formed onto the retina.…”
Section: Discussionmentioning
confidence: 99%
“…The OQAS provides objective measurements of the image formed onto the retina. It combines quantification of ocular media transparency and optical aberrations [16]. They found that OQAS parameters significantly correlated with CDE and ultrasound time, only for pure nuclear cataracts.…”
Section: Discussionmentioning
confidence: 99%